Preferred learning styles for digital native and digital immigrant visitors in the Malaysian music museum / Mohd Nasiruddin Abdul Aziz ... [et al.] - Abdul Aziz, Mohd Nasiruddin; Harun, Siti Norlizaiha; Baharom, Mohd Khairi; Kamaruddin, Norfadilah (Universiti Teknologi MARA, 2020)
The majority of museum experts have agreed that museums are informal learning environments, however, most of the previous studies on digital learning have focused on formal education institutions instead of informal environments. Hence, adapting the new fast-changing technology in museum learning has become one of the major challenges for the digital native and digital immigrant populations due to their different learning styles. These two generations have different levels of thinking patterns, experiences, and digital exposure that lead to different levels of technology accessibility in the learning environment. Therefore, the aim of this study was to investigate the preferred learning styles of museum visitors in the Malaysian context based on the learning styles of digital natives and digital immigrants. A total of 265 respondents participated in this study representing the population of N=792 at the Malaysian music museum in the data collection process. These descriptive results on the cross-tabulation analysis from the survey indicated that most of the visitors preferred the digital natives’ learning styles compared to the digital immigrants’, regardless of personal factors (gender, age, nationality, education level, or occupation). Thus, museum institutions should take the necessary steps to enhance or maintain the learning approach for digital natives with elements of entertainment and fun, provide internet connection, less text, out of school environment, digital use, and multi-task activities for skills enhancement. The minority of digital immigrants are suggested to assimilate and become part of the digital native group to stay relevant in this digital era.